Предмет: Алгебра,
автор: maks2502
найдите сумму корней уравнения 2х(х-2)=(х+1)^2-17
Ответы
Автор ответа:
0
2х(х-2)=
-17
-4х=
+2х+1-17
-6х=-16
Дальше по теореме Виета
х1+х2=6
х1*х2=-16
х1=-2
х2=8
Сумма корней=х1+х2=8-2=6
Дальше по теореме Виета
х1+х2=6
х1*х2=-16
х1=-2
х2=8
Сумма корней=х1+х2=8-2=6
Автор ответа:
0
Вместо N - (х+1) в квадрате
Похожие вопросы
Предмет: Русский язык,
автор: dvs2504
Предмет: Математика,
автор: ganmat09
Предмет: Биология,
автор: dianatishchenko03050
Предмет: Математика,
автор: DanilVolkov12
Предмет: Биология,
автор: мэриита